The Function of Saniri as a Means of Controlling Village Development - Titaley, Elsina; Muhammad Nur, Abubakar; Ruusniel Alfons, Christwyn (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
The saniri institution is a traditional governance body in Maluku, particularly in Central Maluku, responsible for formulating village (negeri) programs, drafting regulations, electing the village head (raja), and overseeing the negeri government’s implementation of development initiatives. Despite its long-standing role and adherence by indigenous communities, concerns have emerged regarding its effectiveness in governance oversight. This study examines the implementation of the saniri’s control function in overseeing development projects in Lumoli Negeri, West Seram Regency. Employing qualitative research methods, findings reveal that the community, as represented by key informants, expresses dissatisfaction with the saniri’s supervisory role. Many perceive that development efforts have failed to meet expectations due to the saniri’s lack of oversight, resulting in underutilized infrastructure and facilities. This study seeks to identify the underlying factors that hinder the saniri’s ability to perform its control function and explore strategies to strengthen its governance role. Enhancing the saniri institution's effectiveness is crucial to ensuring that village development initiatives are successfully implemented and fully utilized by the community.